Simulering er ikke til å spøke med: Helsefagstudenters erfaringer fra tverrprofesjonell teamtrening med bruk av simuleringsmetodikk - Breivik, Marit; Johnsgaard, Tone; Reime, Marit Hegg (Nordisk tidsskrift for helseforskning, 2016)
Simulation is no joke: Healthcare students’ experiences of interprofessional team training using simulation methodology Interprofessional learning through simulation involves different professions who learn with, from and about each other. This study describes healthcare students’ experiences with interprofessional team training. Three focus group interviews were conducted with medical students and nursing students from the bachelor program and the postgraduate program. Data were analyzed according to the method of qualitative content analysis by Graneheim and Lundman. The findings show that making mistakes seems to be beneficial to the quality of patient care as it made the students more vigilant when they returned to clinical practice. Simulated settings seem to be a powerful arena for learning patient safety practices and facilitating transfer of this awareness to clinical practice. The findings also show that the various professions have inadequate knowledge of each other’s expertise. Interprofessional learning through education appears to be necessary for the health professions to strengthen their ability to work together in the future.